Signifikansi Keteladanan Orang Tua Terhadap Pertumbuhan Rohani Anak - Yohana Lanu; Riste Tioma Silaen (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The example of faith from parents greatly impacts the firmness of the faith of children when they are adults. Therefore, the purpose of this research is to help parents implement their exemplary faith effectively. For this reason, the researcher examines the exemplary figures of Ayub and Yusuf in setting an example of their faith when they were in a downturn. So that their example can be used as a reference for Christian parents in particular. In addition to the exemplary faith of Bible figures, the author also examines the psychology of child development. This is meant to help parents to be able to provide an example of their faith in accordance with the development of their child so that the example becomes effective and has a significant impact. This research also provides knowledge on how parents implement this example holistically based on Bible knowledge and also the psychology of child development. So that the right ways are known for parents in giving exemplary faith to their children.